Causal Impact of Government Policy in Stock Market of Nepal - Ojha, Bhoj Raj (Management Dynamics, 2019)
This study is directly related to the semi-strong form of market efficiency. The efficient market hypothesis suggests that stock markets are “informationally efficient”. That is, any new information relevant to the market is spontaneously reflected in the stock prices. A consequence of this hypothesis is that past prices cannot have any predictive power for future prices once the current prices have been used as an explanatory variable. In other words the change in future prices depends only on arrival of new information that was unpredictable today hence it is based on surprise information. It examines the relationship between fiscal policy and stock index in Nepal with using data from 2003 to 2019. This research use market model to determine the statistical relationship. Overall the independent variable government policy poses significant relationship with stock index in Nepal.